Effectiveness of calcific band keratopathy treatment with Ethylenediaminetetraacetic acid combined with cataract extraction in pediatric patients (Ukrainian Journal of Ophthalmology, 2024)
Purpose. To demonstrate the effectiveness of combined surgery including calcific band keratopathy (CBK) treatment followed by cataract extraction with intraocular lens (IOL) implantation in pediatric patients, assessed through preoperative and postoperative best-corrected visual acuity (BCVA) and changes in corneal transparency.Methods. This retrospective study was conducted on the medical records of patients treated for CBK combined with cataract secondary to chronic uveitis between January 2018 and December 2020. The study included 15 eyes of 14 pediatric patients. Clinical parameters recorded included age, primary diagnosis, and preoperative and postoperative BCVA using a Tumbling E chart. Postoperative data were collected at 3 days, 6 months, and 12 months after surgery.Results. Preoperative BCVA averaged 2.03 ± 0.69. On the 3rd postoperative day, BCVA improved to 0.82 ± 0.39, with further improvements to 0.78 ± 0.43 at 6 months and 0.69 ± 0.45 at 12 months. The mean BCVA increased by 2 lines, and BCVA improved by 6 lines within one year postoperatively. Recurrence of CBK was observed in 3 eyes (20%) at 6-month follow-up.Conclusion. Simultaneous EDTA chelation of calcium plaques and phacoaspiration with IOL implantation is an effective and safe treatment for CBK combined with cataract in pediatric patients. This combined approach resulted in significant improvements in visual acuity and corneal transparency and symptomatic relief. However, the high recurrence rate indicates the need for further research.
Keywords: Calcific band keratopathy; cataract; Ethylenediaminetetraacetic acid